INFLUENCE OF REDUCING BIS RECOMMENDED DIETARY PROTEIN LEVELS ON GROWTH PERFORMANCE, CARCASS CHARACTERISTICS AND PRODUCTION ECONOMICS OF BROILER* (Indian Journal of Animal Production and Management, 2013)
A feeding trial was conducted to reduce to the feeding cost without affecting the growth performance of broiler. At three weeks age, 80 chicks were assigned to two dietary protein treatments namely TB (control) and TP (phase fed), each comprising 2 replicates of 20 chicks. Chicks in TB (control) were fed as per BIS (1992) specifications, while chicks in TP from 3 weeks onward were offered a series of diets with decreasing protein levels at weekly interval to the end of experimentation. Results indicated that reducing dietary protein with advancement of age improved economics of broiler production without affecting growth performance.
Keywords: Broiler; BIS feeding; Phase feeding; Growth performance; Economics